Shrub aboveground biomass and Leaf Area Index maps, Trail Valley Creek Watershed, Northwest Territories [Canada], 2018 to 2019 - Chang, Qianyu; Zwieback. Simon; Berg, Aaron; DeVries, Ben (Borealis, 2021)
As the shrub cover expands across the Arctic tundra with climate warming, an accurate and cost-effective tool to quantitatively map the shrub cover is needed. This dataset and the associated study explore the potentials of L-band SAR (Synthetic Aperture Radar) satellite image (ALOS-2) in estimating Arctic shrub biomass and leaf area index (LAI). This dataset includes in-situ measurements of shrub canopy parameters and the ALOS-2 derived maps of birch shrub biomass and LAI in Trail Valley Creek watershed, Northwest Territories.